2023
DOI: 10.1002/prop.202300023
|View full text |Cite
|
Sign up to set email alerts
|

Complexity‐Free Anisotropic Solution of Buchdahl's Model and Energy Exchange Between Relativistic Fluids by Extended Gravitational Decoupling

Abstract: In this work, we present an anisotropic generalization of the Buchdahl static stellar model by implementing the method of extended gravitational decoupling and further requirement of vanishing complexity (Herrera, Phys Rev D 97:044010,2018). Starting off with a general spherically symmetric static metric with two unknown gravitational potentials, we impose the condition of vanishing complexity which then reduces the problem to a single-generating metric function [Contreras and Stuchlik, Eur. Phys. J. C (2022) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…Maurya et al [65] adopted this metric and discussed eight different cases for Buchdahl's dimensionless parameter and found all of them valid at every point within the interior geometry. Various authors used this metric to produce viable as well stable charged/ uncharged interiors in the contexts of  and   f , ( ) theory [66][67][68]. This metric is adopted as follows…”
Section: Buchdahl Solution and Boundary Conditionsmentioning
confidence: 99%
“…Maurya et al [65] adopted this metric and discussed eight different cases for Buchdahl's dimensionless parameter and found all of them valid at every point within the interior geometry. Various authors used this metric to produce viable as well stable charged/ uncharged interiors in the contexts of  and   f , ( ) theory [66][67][68]. This metric is adopted as follows…”
Section: Buchdahl Solution and Boundary Conditionsmentioning
confidence: 99%
“…Considering the influence of the parameter σ, it is observed that increasing its value significantly increases both the pressure components P P , r { } ^, while ò and Δ eff undergo a mild increase as σ rises as described in figures 6-8. The exchange of energy between the relativistic fluid configurations T αβ and Θ αβ in the context of EGD-scheme has been a topic of great interest [51,52,70]. Understanding the dynamics of energy transfer among various fluid components enables us to scrutinize phenomena such as gravitational waves and the evolution of these relativistic systems.…”
Section: Summary and Discussionmentioning
confidence: 99%